Investigating the role of the principal's individualized consideration and intellectual stimulation in shaping the academic performance of students in the secondary schools of Sidama Region, Ethiopia - Dukamo Dessie Dalkie; RJ (Nico) Botha (Eximia, 2024)
The study sought to investigate the principal's perceptions and actions regarding individualized consideration and intellectual stimulation and their implications for students' academic progress. The study was guided by the following research question: How do school principals' transformational leadership strategies improve students' academic progress in Ethiopia's Sidama region? The study used a convergent parallel mixed research design. The data collection strategy was sound, with a modified questionnaire based on the MLQ used in the quantitative phase and an open-ended semi-structured interview in the qualitative phase. The study's dependent variable was student academic performance, while the independent variable was transformational leadership's individualized consideration (IC) and intellectual stimulation (IS) behaviors. The study's target participants were 95 principals and 5956 teachers. The survey used an appropriate sample approach, with 362 teachers and 91 principals from 24 public secondary schools. The qualitative phase involved ten principals and twenty teachers. The acquired data was analyzed using descriptive and inferential statistics. The study found that principals comprehend and practice transformational leadership behaviors. The study also revealed that the principal's individualized consideration and intellectual stimulation practices significantly impacted students' academic progress. The principal's self-assessment was r =.760 (p<.01), whereas the teachers' perception was r =.583 (p<.01).